Male elk survival, vulnerability, and antler size in a transboundary and partially migratory population. Issue 4 (6th March 2023) - Martin, Hans; Hebblewhite, Mark; Hubbs, Anne; Corrigan, Rob; Merrill, Evelyn H.
Abstract: Migration is a behavioral strategy used by many ungulates to access resources and avoid predation in heterogenous landscapes. If migratory individuals access higher quality forage and avoid predation, then they should attain greater fitness. Migration can also expose individuals following distinct migratory tactics to differential mortality and harvest. We investigated how transboundary migration affected male elk ( Cervus canadensis ) survival and antler size when subjected to harvest with different antler point restrictions (APRs) and year‐round harvest by treaty First Nations in a multi‐carnivore system in Alberta, Canada. We measured antler size and age for 35 unmarked, harvested male elk and 90 global positioning system (GPS)‐collared adult male elk. We also estimated radio‐collared elk survival and cause‐specific mortality (105 elk‐years) from 2018 to 2020. Antler size increased as a non‐linear function of age and exposure to high quality forage for migrants. The biological effect size of exposure to higher quality forage (i.e., lower biomass) obtained by migrants was variable but biologically equivalent to the antler size difference (i.e., 33–54 cm) predicted between 5‐ and 6‐year‐old male elk. Annual mortality rate was 0.304 and the primary cause of death was hunting (cumulative incidence functions [CIF] mortality rate = 0.203, n = 33 mortalities) of which a third was by First Nations treaty harvest (CIF = 0.101, n = 12). Non‐human‐caused mortality was rare (CIF = 0.015); only 2 males died because of predation by wolves ( Canis lupus ). Six‐point APRs resulted in lower annual survival rates ( S = 0.42) for male elk with ≥6 antler points, which were usually >4 years of age. Harvest risk increased by 20% for every 1‐km closer to an access road. Elk harvested by licensed recreational or First Nations hunters were similar with respect to male elk age, antler size, date, and location. There was very little evidence that multiple species of large carnivores influenced male elk survival. These results indicate forage quality and vulnerability to harvest by humans influence male elk age structure, and hence antler size, of transboundary and partially migratory populations, even in carnivore‐rich complex systems. Abstract : We studied male elk survival in a migratory, transboundary and multi‐carnivore system at the Ya Ha Tinda adjacent to and in Banff National Park, Alberta, Canada. Elk were harvested under a 6‐point antler point rule, which strongly limited survival of males >4 years old and harvest was responsible for almost all mortality for this group, despite high predation on females by wolf and grizzly bears.